EMPOWERMENT OF LOCAL PLANTS AS BEAUTY PRODUCTS TO INCREASE MSME INCOME - tutik tutik; Aurilia Triani Aryaningtyas; Yustina Denik Risyanti (Enrichment : Journal of Management, 2021)
This study intends to describe business opportunities for beauty products made from local plants to increase the income of MSME actors in Cikaso Village. The technique used in collecting data is by interviewing, observing and analyzing qualitatively descriptive. The results of this study conclude that the business opportunity for beauty products is very wide open in line with the development of people's needs for traditional products. With the support of Cikaso's fertile natural wealth and large yards in almost every home, making the process of making beauty products is not difficult. However, in the midst of government support to empower beauty products made from local plants, it is hampered by people's distrust of producing them.